Lymphocyte-Peppered Sclerotic Collagen: An Additional Histological Clue in Lichen Sclerosus, Morphea, and Systemic Sclerosis. (21st December 2021) - Yadav, Deepika; Agarwal, Shipra; Thakur, Shilpi; Ramam, M.
Abstract : Background: "Line sign, " "cookie cutter sign, " "square biopsy sign, " "high eccrine glands sign" have been previously described in morphoea and lichen sclerosus. We found focal areas of thickened collagen bundles with lymphocytes interspersed between them in several biopsies of these conditions. Materials and Methods: We reviewed slides of sclerosing disorders obtained from the archives of the pathology department in our hospital for the period 2013–2019. Results: A total of 73 slides including 40 of lichen sclerosus, 24 of morphea, 2 of lichen sclerosus-morphea overlap, and 7 of systemic sclerosis were evaluated. Lymphocytes were noted between sclerotic collagen bundles in 46 (63%) slides, being most common in lichen sclerosus (80%, 32/40) followed by morphea (50%, 12/24), whereas it was seen in one case each of lichen sclerosus with morphea overlap (50%, 1/2) and systemic sclerosis (14.3%, 1/7). The finding was noted in the upper dermis in 20 of 32 (62.5%) slides of lichen sclerosus and in both the superficial and deep dermis in 11 (91.7%) of 12 slides of morphea. Conclusion: Lymphocyte-peppered sclerotic collagen may be a useful histological clue to the diagnosis of lichen sclerosus, morphea, and systemic sclerosis.